Role of fruit and vegetables for the mental health of children: a systematic review - Dominika Guzek; Dominika Głąbska; Barbara Groele; Krystyna Gutkowska (National Institute of Public Health - National Institute of Hygiene, 2020)
Background. About 10-20% of children and adolescents worldwide experience a mental health problems, while among the factors which may be preventive, there is a diet, especially fruit and vegetables intake. Objective. The aim of the study was to conduct a systematic review of the observational studies analyzing the association between the fruit and vegetables intake and the mental health in pre-schoolers and school-aged children. Material and methods. The systematic review was conducted based on PubMed and Web of Science databases, while the human studies, published in English until June 2019, conducted in populations of pre-schoolers and/ or school-aged children, verifying the influence of fruit and/ or vegetables and products (e.g. juices) intake on a various aspects of mental health were included. Results. The number of 12 studies were included, while a wide area of aspects of mental health was taken into account, including general well-being, emotions, stress, behavioral difficulties and problems, as well as depressive symptoms, or depressive symptoms combined with anxiety. Conclusions. In majority of studies included to the systematic review of the observational studies analyzing the association between the fruit and vegetables intake and mental health in pre-schoolers and school-aged children, the supposed positive influence was confirmed. However, it must be indicated that it was studied only in a few research and the issue must be analyzed in other populations. At the same time, in a number of studies, not fruit and vegetables intake alone was stated to be beneficial, but rather a more general dietary pattern, including also other elements of healthy diet and healthy lifestyle.